Evaluation of the efficacy of apoE gene transfection - Białoszycka, Żanna; Białoszycka, Monika; Pachevska, Alisa; Istoshyn, Valerij; Biloshytska, Alina; Simonova, Irina (Quality in Sport, 2024)
Introduction: Pathology of organs of the male reproductive system remains one of the most urgent problems of modern medicine, which is associated not only with patients’ impaired quality of life, but also with high rates of male infertility, which tends to increase. The aim: To evaluate the efficacy of apoE gene transfection on the morphofunctional state of rat testes in experimental atherosclerosis. Materials and methods: The study was conducted on 30 sexually mature male rats weighing 150-170 grams. Experimental animals were divided into 3 groups. Group 1 - intact animals. Group 2 – animals with experimental atherosclerosis; Group 3-animals with experimental atherosclerosis, which were intramuscularly injected with the apolipoprotein E gene at a dose of 50 μg of DNA per animal on the first day of modeling atherosclerosis. To study the efficiency of apolipoprotein E gene transfection on morphofunctional changes in testes, the following research methods were used: 1) histological; 2) biochemical; 3) reverse transcriptase PCR diagnostic method. Results and discussion. Experimental cholesterol loading leads to impaired lipid metabolism, decreased serum testosterone levels, degenerative and dystrophic changes in the testis of experimental rats, which is manifested by luminal occlusion of blood vessels, overgrowth of connective tissue in the organ interstitium, decreased number and qualitative change of Sertoli and Leydig cells, as well as spermatogenic epithelium thinning and inhibition of gamete maturation process in it. Conclusions: intramuscular transfection of the apoE gene inhibits lipid metabolism disorders and has a positive effect on the morphofunctional state of the testes of experimental animals.